Time measurements with a mobile device using sound. (16th February 2018) - Wisman, Raymond F; Spahn, Gabriel; Forinash, Kyle
Abstract: Data collection is a fundamental skill in science education, one that students generally practice in a controlled setting using equipment only available in the classroom laboratory. However, using smartphones with their built-in sensors and often free apps, many fundamental experiments can be performed outside the laboratory. Taking advantage of these tools often require creative approaches to data collection and exploring alternative strategies for experimental procedures. As examples, we present several experiments using smartphones and apps that record and analyze sound to measure a variety of physical properties.